Edukasi tentang Sanitasi dan Kesehatan Lingkungan pada Masyarakat Kelurahan Buntusu Kota Makassar - Nursinah, Andi; Nurhaedah, Nurhaedah; Mustamin, Rini; Hilal, Achmad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
BUNTUSU was originally a village which in 1958 was still part of the Moncongloe Maros district, then in 1961 it became part of the Tamalanrea neighborhood, Biringkanaya District, Ujung Pandang Municipality. The aim of this PKM is to increase partners' knowledge about drainage construction to dispose of dirty household water that is safe for the environment, introduce partners to the tools and materials used to make drainage construction to dispose of household dirty water that is safe for the environment, and improve partners' skills in making construction drainage to dispose of dirty household water that is safe for the environment. The methods used are lectures, discussions and questions and answers, training methods used are demonstrations, discussions and questions and answers. The results of the PKM achieved are as follows. The results of this PKM activity can be described through the role of community social capital as a form of local knowledge, which can be used as a means of socializing the importance of awareness of environmental sanitation. The process of increasing community knowledge in improving environmental sanitation is carried out through three approaches, namely socialization, assistance and planning for making trash cans and making latrines. Partners have knowledge about drainage construction to dispose of household dirty water that is safe for the environment. Partners recognize the tools and materials used to make them. drainage construction to dispose of household dirty water that is safe for the environment, and a drainage construction for the disposal of household dirty water that is safe for the environment has been built in one of the community residences which was built directly.